Hubungan Posisi Kerja dan Masa Kerja dengan Keluhan Low Back Pain pada Pekerja Batu Bata - Mulyani, Riri; Muslim, Burhan; Mukhlis, Mukhlis; Gusti, Awalia; Lindawati, Lindawati (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Padang, 2025)
Every workplace, both formal and informal, has hazards and risks that can lead to accidents and occupational health. One of the informal industries is the brick industry that is at risk of occupational diseases, namely Low Back Pain, which is pain felt in the lower back. One of the brick printing factories is located in Nagari Ganggo Hilia, Bonjol District. In 2022, 65.7% of workers in Bonjol District experienced complaints of low back pain. The purpose of the study is to determine the relationship between work position and working period with complaints of Low Back Pain in brick workers in Bonjol District, Pasaman Regency in 2024.The type of research is a quantitative research with a cross sectional approach in January – June 2024. Sampling by census, the entire population was sampled as many as 35 people. Data was collected through interviews and observations.. Univariate and bivariate data were analyzed using the Chi-Square statistical test. The results of the study showed that 68.6% of brick workers experienced Low Back Pain complaints, as many as 62.9% of brick workers did work with high risk and very high body positions and as many as 65.7% of brick workers with a long working period. The bivariate results showed that there was a relationship between work position (p=0.001) and working period (p=0.002) with Low Back Pain complaints. To reduce the risk of low back pain complaints, brick owners should provide work tools that support workers to work ergonomically such as providing seats so that they do not stand when making bricks and regulating workers' working hours according to the conditions of the work environment.